Implementasi Praktek Perawatan Memandikan Bayi Dan Perawatan Tali Pusat Bayi Baru Lahir Untuk Mahasiswa - Parwati, Dewi; M, Warda; Nurhayati, Nurhayati; Dhamayanti, Reffi; Wati, Wati; Irmayani, Irmayani; Nainggolan, Nurcahaya (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Students' knowledge and skills to be able to perform baby bathing and umbilical cord care properly and correctly are very much needed in carrying out health services. The purpose of Community Service is to assess and find out the description of students' skills on how to bathe babies properly and safely. The method used in Community Service activities is a direct examination of students who are implementing the practice of baby bathing and umbilical cord care for newborns. The results of community service obtained the level of student skills in the practice of baby bathing and umbilical cord care for newborns are skilled 23 students (77%) and unskilled as many as 7 students (23%). The conclusion is that the increase in students' skills and knowledge in bathing babies from the beginning which was still lacking and finally students know and understand the importance of carrying out health services.